Mini-KiSS Online: an Internet-based intervention program for parents of young children with sleep problems – influence on parental behavior and children's sleep - Schlarb AA (Dove Medical Press, 2012)
Angelika A Schlarb1,2,*, Isabel Brandhorst1,* 1University of Tuebingen, Faculty of Science, Department of Psychology, Tuebingen, 2University of Koblenz-Landau, Department of Psychology, Landau, Germany*The authors contributed equally to this workPurpose: Behavioral sleep problems are highly common in early childhood. These sleep problems have a high tendency to persist, and they may have deleterious effects on early brain development, attention, and mood regulation. Furthermore, secondary effects on parents and their relationship are documented. Negative parental cognition and behavior have been found to be important influencing factors of a child's behavioral sleep problems. Therefore, in the current study we examined the acceptance and efficacy of a newly developed Internet-based intervention program called Mini-KiSS Online for sleep disturbances for children aged 6 months to 4 years and their parents.Patients and methods: Fifty-five children (54.54% female; aged 8–57 months) suffering from psychophysiological insomnia or behavioral insomnia participated in the 6-week online treatment. Sleep problems and treatment acceptance were examined with a sleep diary, anamnestic questionnaires, a child behavior checklist (the Child Behavior Checklist 1.5–5), and treatment evaluation questionnaires.Results: The evaluation questionnaires showed a high acceptance of Mini-KiSS Online. Parents would recommend the treatment to other families, were glad to participate, and reported that they were able to deal with sleep-related problems of their child after Mini-KiSS Online. Parental behavior strategies changed with a reduction of dysfunctional strategies, such as staying or soothing the child until they fell asleep, allowing the child to get up again and play or watch TV, or reading them another bedtime story. Frequency and duration of night waking decreased as well as the need for external help to start or maintain sleep. All parameters changed significantly, not only in the questionnaires but also in the sleep diary.Conclusion: Mini-KiSS Online is shown to be a highly accepted and effective treatment to change parental behavior and reduce behavioral sleep problems in early childhood.Keywords: insomnia, childhood, behavioral insomnia of childhood, online treatment, parental behavior